THE INFLUENCE OF PERSON ORGANIZATION FIT ON TURNOVER INTENTION WITH EMPLOYEE ENGAGEMENT AS A MEDIATION VARIABLE AT EMPLOYEES PT. MANDALA MULTIFINANCE Tbk SAUMLAKI BRANCH - Gerrit M. Pentury; Victor Huwae (Jurnal Ekonomi, 2023)
This study aims to examine and analyze the effect of person organization fit on employee engagement, analyze the effect of person organization fit on turnover intention, analyze the effect of employee engagement on turnover intention, analyze the effect of person organization fit on turnover intention through employee engagement. This research was conducted on employees of PT. Mandala Multifinance Tbk. Saumlaki Branch. The sample used amounted to 35 respondents. The research method used is a quantitative research method. The distribution of questionnaires was measured using a Likert scale. Methods of data analysis using toolsanalysisPartial Least Squareprocessing through Smart PLS software version 4. The results showed that person organization fit had an effect on employee engagement, there was an effect of person organization fit on turnover intention, there was an effect of employee engagement on turnover intention, there was an effect of person organization fit on turnover intention through employee engagement.